Patients’ Diets and Preferences in a Pediatric Population with Inflammatory Bowel Disease - Timothy J Green; Robert M Issenman; Kevan Jacobson (Canadian Journal of Gastroenterology)
PURPOSE: To determine the dietary practices of the pediatric inflammatory bowel disease population at the Children's Hospital of the Hamilton Health Sciences Corporation and the reported effectiveness of those diets.